1999
DOI: 10.1123/apaq.16.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Assisted Instruction in a Motor Skill Program for At-Risk Preschool Children

Abstract: The purpose was to investigate the effectiveness of parental involvement on the acquisition of object-control skills of preschool children who are at risk for developmental delay or academic failure. The experimental group (n = 15) participated in an 8-week motor skill intervention program consisting of two 45-min lessons per week delivered by the children’s parents. The control group (n = 12) participated in the regular motor skill program, which consisted of movement songs delivered by the parents. All child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 12 publications
4
68
0
5
Order By: Relevance
“…Overall, studies on motor skill interventions such as SKIP show that when motorically delayed preschool children received well designed structured motor skill instruction, significant improvements in their FMS resulted which to remediated these delays (Goodway & Branta, 2003;Hamilton et al, 1999;Martin, Rudisill, & Hastie, 2009;Robinson & Goodway, 2009). The timeframe of these programs has typically been somewhere between 8 to 12 weeks (16 to 24 lessons) with 30-45 minutes per session.…”
Section: Effects Of Motor Skill Instruction On the Fms Of Disadvantagmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, studies on motor skill interventions such as SKIP show that when motorically delayed preschool children received well designed structured motor skill instruction, significant improvements in their FMS resulted which to remediated these delays (Goodway & Branta, 2003;Hamilton et al, 1999;Martin, Rudisill, & Hastie, 2009;Robinson & Goodway, 2009). The timeframe of these programs has typically been somewhere between 8 to 12 weeks (16 to 24 lessons) with 30-45 minutes per session.…”
Section: Effects Of Motor Skill Instruction On the Fms Of Disadvantagmentioning
confidence: 99%
“…However, there are disparities in the opportunity to do this. A growing body of research shows that young children who come from disadvantaged and poor environments show significant developmental delays in their FMS, including locomotor (10 th -17 th percentile) and manipulation (16 th percentile) skills (Goodway & Branta, 2003;Goodway, Crowe & Ward, 2003;Goodway et al, 2010;Hamilton et al, 1999;Robinson & Goodway, 2009). This has been found true for African American and Hispanic children, across geographic region, and urban and rural environments (Goodway & Branta, 2003;Goodway et al, 2010;Hamilton et al, 1999;Robinson & Goodway, 2009).…”
Section: Disadvantaged Preschoolers Demonstrate Developmental Delays mentioning
confidence: 99%
See 1 more Smart Citation
“…Estudios similares han encontrado mejoras en el desarrollo motor, en poblaciones de la misma edad luego de 4, 9 ó 12 semanas de un programa de intervención motriz (Goodway & Branta, 2003;Hamilton, Goodway & Haubenstricker, 1999;Valentini & Rudisill, 2004).…”
Section: Discussionunclassified
“…These articles have argued that parents should play a more central role in motor intervention (Darrah, Law & Pollack, 2001); provided data indicating that parents are comfortable with this role (Sayers, Cowden & Sherrill, 2002); and demonstrated that parent involvement can have a positive impact on motor intervention effectiveness (Hamilton, Goodway & Haubenstricker, 1999;Ketelaar, Vermeer, Helders & Hart, 1998;Torres & Buceta, 1998). However, given the low level of effort that went into to parent involvement in our study, it is not surprising that intervention had no effect on parent-child interaction or that parent participation did not affect intervention outcomes.…”
Section: G Mahoney and F Perales • Parents And Motor Interventionmentioning
confidence: 99%